THE LEARNING MANAGEMENT BY INSTRUCTIONAL MODEL BASED ON SIMPSON’S PRACTICE SKILL OF FOOTBALL FOR THE EIGHTH GRADE STUDENTS - Mopim, Anuphab; Laoakka, Thanarat (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The purposes of this research were to: 1) develop the learning management by instructional model based on Simpson’s practice skill of football for the eighth grade students to be effective according to the criterion of 70/70 2) study the development of Football practice skillsfor the eighth grade Studentsstudying with Simpson’s Practical Skills Learning Management. The target audience is 17 eighth grade students at Watthayaim School Phutthaisong Sub-district Phutthaisong District Buriram Province in the first semester of the academic year 2021. The research instruments were: 1)learning management plan by Instructional Model Based on Simpson’s practice skill of Football eighth grade, 6 plans, each 2 hours long, for a total of 12 hours 2) Football Skills Assessment, 7 issues. 3) football skills test, 6 issues, is completion form. The statistics used to analyze the data were percentage, mean, and standard deviation. The research findings revealed that: 1. the learning management by Instructional Model Based on Simpson’s practice skill of Football for the eighth grade students has an efficiency of 78.50/79.78, whichwasgreater than the criterion of 70/70. 2. The development of football practice skillsfor the eighth grade studentsstudying with Simpson’s practical skills learning managementduring the course, the mean score was 46.10, which equaled 76.67 percent and the post-test mean score was 38.29, which equaled 79.78 percent, meaning that the learning management of the Simpsons practical skills. As a result, the students’ soccer practice skills were higher and met the criteria by 70 percent.